1974
DOI: 10.1042/bj1420401
|View full text |Cite
|
Sign up to set email alerts
|

Production and utilization of acetate in mammals

Abstract: 1. In an attempt to define the importance of acetate as a metabolic precursor, the activities of acetyl-CoA synthetase (EC 6.2.1.1) and acetyl-CoA hydrolase (Ec 3.1.2.1) were assayed in tissues from rats and sheep. In addition, the concentrations of acetate in blood and liver were measured, as well as the rates of acetate production by tissue slices and mitochondrial fractions of these tissues. 2. Acetyl-CoA synthetase occurs at high activities in heart and kidney cortex of both species as well as in rat liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
190
6
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(206 citation statements)
references
References 34 publications
9
190
6
1
Order By: Relevance
“…Acetate can be generated by the removal of acetyl groups from histones by histone deacetylases 20 and by hydrolysis of Ac-CoA 21 . We thus measured the concentrations of the metabolites involved in these processes and observed orders of magnitude lower concentrations of Ac-CoA than glucose-derived pyruvate, lactate, and acetate ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Acetate can be generated by the removal of acetyl groups from histones by histone deacetylases 20 and by hydrolysis of Ac-CoA 21 . We thus measured the concentrations of the metabolites involved in these processes and observed orders of magnitude lower concentrations of Ac-CoA than glucose-derived pyruvate, lactate, and acetate ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This could be modified by the activity of acetyl-CoA hydrolase, such interference would not substantially affect the 14C02 liberation from [l-14C]pyruvate. The activity, regulation and physiological significance of this enzyme has recently been discussed for liver [23] and adipose tissue [24]. Secondly, factors such as the amount of potassium in the medium and the pH of the medium may be critical as indicated by the studies of Hucho et al [25] who have shown differential effects of these parameters on the activities of pyruvate dehydrogenase kinase and pyruvate dehydrogenase phosphatase in kidney and heart.…”
Section: Radioactive Methodsmentioning
confidence: 99%
“…Only acetate is present in significant amounts in the peripheral blood of nonherbivores and at concentrations lower than in herbivores (R6m6sy and Demign6, 1974). Surprisingly, there is no evident difference in blood concentrations between fed and starved non-herbivores (Knowles et al, 1974). In the rat, the main site of VFA production and absorption is the large intestine, particularly the caecum (R6m6sy and Demign6, 1976).…”
Section: Introductionmentioning
confidence: 96%
“…In the rat, the main site of VFA production and absorption is the large intestine, particularly the caecum (R6m6sy and Demign6, 1976). Besides digestive origin, it has frequently been suggested that endogenous acetate could be produced by various tissues (Knowles et al, 1974 ;Seufert et a/., 1974 ;Buckley and Williatnson, 1977).…”
Section: Introductionmentioning
confidence: 99%